2011
DOI: 10.4081/reumatismo.2009.290
|View full text |Cite
|
Sign up to set email alerts
|

The support of the ultrasonography of the shoulder in the diagnosis of polymyalgia rheumatica with normal erythrocyte sedimentation rate

Abstract: The Polymyalgia Rheumatica (PMR) is a cronic inflammatory syndrome that affects the elderly population and whose diagnosis is mainly based on clinical criteria taking little advantage of the latest innovatory methods of diagnostic imaging, for instance ultrasonography. Although it is generally characterised by increasing of inflammation values as well as pain and stiffness on the shoulder and pelvic girdles, there is a significant percentage of patients with PMR whose erythrocyte sedimentation rate (ESR) is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…Moreover, the studies conducted by Zaccaria et al and Jimenez et al in 2009 identified the absence of significant differences in the US pattern in patients with normal or high erythrocyte sedimentation rate (ESR). In addition, even in the presence of a parallel decrease in the findings, the authors did not find significant correlation between changes of clinical, laboratory and US parameters during the follow-up period [20,26].…”
Section: Ultrasonographic Findings In Pmr Patientsmentioning
confidence: 82%
See 4 more Smart Citations
“…Moreover, the studies conducted by Zaccaria et al and Jimenez et al in 2009 identified the absence of significant differences in the US pattern in patients with normal or high erythrocyte sedimentation rate (ESR). In addition, even in the presence of a parallel decrease in the findings, the authors did not find significant correlation between changes of clinical, laboratory and US parameters during the follow-up period [20,26].…”
Section: Ultrasonographic Findings In Pmr Patientsmentioning
confidence: 82%
“…However, the prevalence of SAD bursitis resulted higher compared to LBT tenosynovitis in the majority of the studies, suggesting this lesion as the inflammatory hallmark in PMR [13,[18][19][20]22,25,26]. Moreover, as reported in Table I, a frequent US finding was the identification of bilateral involvement both at shoulder and hip level [19,21,[25][26][27].…”
Section: Ultrasonographic Findings In Pmr Patientsmentioning
confidence: 99%
See 3 more Smart Citations